Analysis of the Urban Forest Status in Bandar Lampung City - Yusuf, Agung Permada; Darmawan, Arief; Iswandaru, Dian (Jurnal Sylva Lestari, 2019)
Urban forest is one form of green open space. Urban forests play an important role in maintaining the sustainability of ecological functions in a city. This role could only run optimally with the availability of urban forests. The purpose of this study is to analyze the status of land ownership and analyze the efforts that can be made in maintaining urban forests. This study used image analysis, interviews, and field observations. From the results of this study, the status of urban forests based on the Mayor of Bandar Lampung Decree in 2010 had different statuses at each location. The urban forest ownership does not exclusively belong to the government. Of the 5 locations, only 1 location owned by the Bandar Lampung City Government, with 1 location that is not recognized (problematic), 1 location did not have a certificate of rights yet, and 2 other locations were private locations. The best effort that could be made to maintain the existence of urban forests is to control urban forest land as ownership in the name of the City Government with the support of certain regulations that can be done. Keywords: land status, urban forest, Lampung